Utilizing India’s One Billion Dollar Line of Credit Budhi Gandaki, Mahakali III and Bridge over Mahakali – Projects Born and Bred at Singha Durbar? - Pun, S. B. (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
When India’s Prime Minister Narendra Modi offered Nepal 1 billion USD line of credit in August 2014, many Nepalese believed this would be utilized to implement the stalled 6,480 MW Pancheshwar Multipurpose Project. During the September 1996 Mahakali Treaty ratification, the Pancheshwar Project was claimed to make the ‘sun rise from the west’ for Nepal! In fact, the joint press release of the two prime ministers did stress to ‘finalise the DPR of Pancheshwar Development Project and begin implementation of the Project within one year.’ However, it was reported that, India’s External Affairs Secretary, Ms. Sujata Mehta, visited Nepal in November2014 and ‘concluded the terms and conditions for the credit line.’ While there was no word on the Pancheshwar Multipurpose Project, the Budhi Gandaki Hydropower Project suddenly raised its head with the government’s own finance minister strongly justifying it. Similarly, the Mahakali III Irrigation Project from the Tanakpur Barrage and amulti-lane motorable bridge over Mahakali River were also identified as projects to be funded through the Indian line of credit. This article examines the background of these three projects (Budhi Gandaki, Mahakali III, and bridge over Mahakali) and questions whether they were truly born in Singha Durbar, or further away in Delhi. DOI: http://dx.doi.org/10.3126/hn.v16i0.12211 HYDRO Nepal Journal of Water Energy and Environment Issue No: 16 January, 2015 Page: 1-6 Uploaded date: March 1, 2015